ICT as a Game-Changing Toolset for 21st Century Integration and Accessibility of Indian Knowledge System - Prof. Manoj Kumar Saxena, Vikram Bajotra (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Information and communication technologies (ICTs) have become potent tools in the dynamic 21st-century landscape, capable of reshaping economies, educational systems, and society